2017
DOI: 10.1159/000486025
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor 1 Promotes Immunosuppression in Human Non-Small Cell Lung Cancers by Enhancing TGF-Β1 Expression in Macrophage

Abstract: Background: Plasminogen activator inhibitor-1 (PAI-1) has been regarded as a risk factor for thrombosis and atherosclerosis. Since it has been shown that PAI-1 can activate macrophages through Toll-like receptor-4, we sought to investigate the role of PAI-1 in the tumor microenvironment. Methods: The expression and distribution patterns of PAI-1 and transforming growth factor beta (TGF-β) were measured in 60 non-small cell lung cancer (NSCLC) tumors. A statistical correlation analysis was performed between PAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…Consistently with our findings, previous studies have reported that NR4A1 activation was noted in fatty liver disease and atherosclerosis [24,25] and that the genetic deletion of NR4A1 or pharmacological inhibition of NR4A1 retards or prevents the progression of nonalcoholic fatty liver and atherosclerosis [66,67]. Collectively, these observations have demonstrated the sufficiency of NR4A1 to exacerbate chronic metabolic diseases, which may highlight a new method for treating chronic metabolic disorders by targeting NR4A1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently with our findings, previous studies have reported that NR4A1 activation was noted in fatty liver disease and atherosclerosis [24,25] and that the genetic deletion of NR4A1 or pharmacological inhibition of NR4A1 retards or prevents the progression of nonalcoholic fatty liver and atherosclerosis [66,67]. Collectively, these observations have demonstrated the sufficiency of NR4A1 to exacerbate chronic metabolic diseases, which may highlight a new method for treating chronic metabolic disorders by targeting NR4A1.…”
Section: Discussionsupporting
confidence: 92%
“…The NR4A1 activation induced by a high-fat diet promotes Drp1 phosphorylation and Bnip3 transcriptional arrest, selectively stimulating Drp1-mediated mitochondrial fission and inhibiting Bnip3-related mitophagy [24]. In addition, upregulated NR4A1 also induces high-fat associated endothelial dysfunction and atherosclerosis formation by regulating Parkin-mediated mitophagy activity [25]. On this basis, we aimed to investigate whether NR4A1 is upregulated by hyperglycemia and activates Mff-required mitochondrial fission and represses Parkin-related mitophagy, finally leading to mitochondrial dysfunction, glomerular mitochondrial apoptosis, and the development of DN.…”
Section: Introductionmentioning
confidence: 99%
“…Plasminogen is then degraded to plasmin through the activity of PLAT and/or PLAU leading to activation of metalloproteinases and degradation of fibrin. SERPINE1 shows increased expression in a number of cancer subtypes and plays important roles in cell adhesion, invasion, tumor vascularization, radio-resistance, and immunosuppression (Kubala et al, 2018;Zhu et al, 2017). High expression of the plasminogen activation signature correlated with worse OS (p=0.0029) within the TCGA lung adenocarcinoma RNAseq dataset ( Figure 3J).…”
Section: Longitudinal Scrnaseq Profiles Of Cancer Cells Change From Rmentioning
confidence: 98%
“…Several genes in the plasminogen activation pathway were significantly overexpressed (ANXA2, PLAT, PLAUR, PLAU) ( Figure 3H) along with the plasminogen inhibitor SERPINE1 (PAI1) (p<0.0001, Figure 3I, Supplemental Figure 3G). ANXA2 and PLAUR are the receptor proteins in the plasminogen activation cascade and involved in inflammation, angiogenesis, invasion and metastasis, via degradation of the extracellular matrix (Kubala et al, 2018;Zhu et al, 2017). Signaling is initiated when ANXA2 or PLAU binds to PLAT (uTa) or PLAU (uPa), respectively.…”
Section: Longitudinal Scrnaseq Profiles Of Cancer Cells Change From Rmentioning
confidence: 99%
“…EV-A71 VP1 neutralizing antibody (Cat.No.40013-H136) was purchased from Sino Biological (Beijing, China). The NF-κB inhibitor (BAY 11-7082, S2913) (Mosteiro et al 2016) and Smad3 inhibitor (SIS3 HCl, S7959) (Zhu et al 2017) were purchased f r o m S e l l e c k ( S h a n g h a i , C h i n a ) . F l u o r e s c e i n isothiocyanate-dextran (FD4) and dimethyl sulfoxide (DMSO) (V900090) were purchased from Sigma-Aldrich (MO, USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%